2015
DOI: 10.3109/01658107.2015.1072726
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Anti-Myelin Oligodendrocyte Glycoprotein Antibody Seropositive Cases of Optic Neuritis

Abstract: We have studied the clinical picture of anti-aquaporin antibody (AQP4-Ab)-and anti-myelin oligodendrocyte glycoprotein antibody (MOG-Ab)-positive optic neuritis. However, optic neuritis associated with MOG-Abs has not been elucidated using new methods such as cell-based assay. Hence, we conducted a comprehensive investigation on its clinical profile. Serum samples from 70 patients (17 males and 53 females, mean age 43.1 years) with optic neuritis were tested for MOG-Abs by cell-based assay. In MOG-Ab seroposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…The exquisite steroid sensitivity of MOG-ON, reminiscent of that observed with CRION, raises the possibility that CRION could be a manifestation of the MOG-inflammatory demyelinating disease spectrum. This observation was indeed confirmed in more than one study where patients with a clinical diagnosis of CRION or RION were found to have the MOG antibody [ 43 , 51 , 61 , 62 ]. The potential course of demyelinating optic neuropathy is summarized in Figure 1 .…”
Section: Optic Neuritis: From Clinically Isolated Syndrome To Ms supporting
confidence: 53%
See 2 more Smart Citations
“…The exquisite steroid sensitivity of MOG-ON, reminiscent of that observed with CRION, raises the possibility that CRION could be a manifestation of the MOG-inflammatory demyelinating disease spectrum. This observation was indeed confirmed in more than one study where patients with a clinical diagnosis of CRION or RION were found to have the MOG antibody [ 43 , 51 , 61 , 62 ]. The potential course of demyelinating optic neuropathy is summarized in Figure 1 .…”
Section: Optic Neuritis: From Clinically Isolated Syndrome To Ms supporting
confidence: 53%
“…In both the MOG-ON and the MS-ON groups, visual acuity loss during a relapse and the long-term outcome past one year were similar, but they were worse in AQP4-ON group. The less severe prognosis of MOG-ON was confirmed in a study by Matsuda et al, who also showed that the residual deficit was commonly present due to an increased number of relapses per year [ 62 ]. A 2017 study by Stiebel-Kalish et al compared the visual acuity, field defect, and thickness of the retinal nerve fiber layer over time between a group of MOG-ON and AQP4-ON.…”
Section: Optic Neuritis: From Clinically Isolated Syndrome To Ms mentioning
confidence: 89%
See 1 more Smart Citation
“…With respect to VA after treatment, the response to treatment was evidently good in the MOG-Abepositive group, with visual recovery to 0.5 (decimal VA, 0.3) or higher in 82% of the patients and 0.2 (decimal VA, 0.7) or higher in 74% of patients. Matsuda et al 10 reported good visual outcomes in MOG-Abepositive optic neuritis patients. Furthermore, Zhao et al 23 also reported good VA outcomes after treatment in MOG-Abepositive optic neuritis patients.…”
Section: Visual Function and Treatmentmentioning
confidence: 98%
“…Endo et al 34 reported that in Japan, AQP4-Abepositive optic neuritis recurs 1.5AE2.3 times, and 46.8% of all patients show a bilateral decrease in VA. For MOG-Abepositive optic neuritis also, a high percentage of bilateral recurrent disease has been reported. 10,22,23,51 Therefore, in evaluating optic neuritis, laterality and recurrence are very important findings. Of 531 patients analyzed herein, 353 (66.5%) showed primary (first episode of) optic neuritis, and long-term follow-up was not available for these patients.…”
Section: Limitations Of This Study and Future Perspectivementioning
confidence: 99%